1990
DOI: 10.1007/bf00164007
|View full text |Cite
|
Sign up to set email alerts
|

Forager specialization and the control of nest repair in Polybia occidentalis Olivier (Hymenoptera : Vespidae)

Abstract: We measured patterns of individual forager specialization and colony-wide rates of material input during periods of response to experimental nest damage and during control periods in three colonies of the tropcial social wasp Polybia occidentalis.(1) Most foragers specialized on gathering a single material. While active, foragers rarely switched materials, and most switching that did occur was between functionally related materials -prey and nectar (food materials) or wood pulp and water (nest materials).(2) I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 23 publications
(27 reference statements)
1
32
0
Order By: Relevance
“…However, the onset of outside-nest tasks coincides with worker ovary resorption (32), suggesting that JH could affect both. Although P. occidentalis resembles honey bees in having a well defined age polyethism and large colony size, it resembles Polistes and other primitively eusocial genera in not having morphologically distinct castes, with caste likely determined, as in other primitively eusocial swarming species, in the adult stage (33)(34)(35).…”
Section: Limitations Of Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the onset of outside-nest tasks coincides with worker ovary resorption (32), suggesting that JH could affect both. Although P. occidentalis resembles honey bees in having a well defined age polyethism and large colony size, it resembles Polistes and other primitively eusocial genera in not having morphologically distinct castes, with caste likely determined, as in other primitively eusocial swarming species, in the adult stage (33)(34)(35).…”
Section: Limitations Of Previous Studiesmentioning
confidence: 99%
“…1, 3, and 4) is most apparent in ''highly eusocial'' species, or species with large colonies and morphologically discrete workers and queens, but it also occurs in ''primitively eusocial'' species, those with behaviorally but not morphologically distinct castes (1,5). Task allocation among an age cohort of workers is known to be sensitive to genetic variation (6,7) and to colony conditions, such as the size and age of the brood, nest damage, presence of predators and parasites, and the size and age of the worker population (2, 5, 8-13). Given the many factors that can affect task performance, the expression of age polyethism is highly variable both within and between species.…”
mentioning
confidence: 99%
“…These workers are called specialists or elite (Robson and Traniello, 1999). There is empirical evidence in favor of the existence of specialization in Hymenoptera (Rissing, 1981;Calderone and Page, 1988;O'Donnell and Jeanne, 1990). Kolmes and Sommeijer (1992), working with the stingless bee M. favosa, found that the construction of brood cells is a task performed by an elite group of workers.…”
Section: Diverse Approaches To the Study Of Division Of Labormentioning
confidence: 99%
“…Individual differentiation has been studied in other Hymenoptera, e.g. in ants (Gordon, 1999), wasps (O'Donnell and Jeanne, 1990) and in Apis bees (Visscher and Camazine, 1999). In stingless bees, intranidal individual behavior has been studied in Melipona favosa (Sommeijer et al, 1982;Kolmes and Sommeijer, 1992), M. bicolor (Bego, 1983), Trigona (Tetragonula) minangkabau (Inoue et al, 1996), and M. subnitida (Koedam et al, 1999).…”
mentioning
confidence: 99%
“…They react to changes in colony need by initiating food collecting at younger age or by increasing their foraging activity when the food reserves are low (Fewell and Winston, 1992). Also, additional workers are allocated to nest repair when the nest is damaged (O'Donnell and Jeanne, 1990). Individuals alter the colony status by increasing the amount of food that is stored or by repairing the nest.…”
Section: Introductionmentioning
confidence: 99%